Basic Research, Openness, and Convergence - Hans Gersbach; Maik T. Schneider; Olivier Schneller (ETH Zurich, CER-ETH - Center of Economic Research, 2010)
We study a model where economic growth is fueled by public basic-research investment and the importation of leading technology from foreign countries. In each period, the government chooses the amount of basic research, balancing the cost and benefits of stimulating growth through both channels. We establish the existence of steady states and the long-run share of technologically advanced sectors in the economy. Then, we explore how different degrees of openness affect long-term incentives to invest in basic research. Our main insight is that higher openness tends to encourage more investment in basic research which, in turn, yields a larger share of leading sectors. If, however, there are prospects of importing large technology advancements, highly open countries will reduce basic research as such imports become particularly valuable.
Keywords: O31; O38; 330; basic research; openness; economic growth; Grundlagenforschung; Technologiepolitik; Technologietransfer; Handelsliberalisierung; Wirtschaftswachstum; Wirtschaftliche Konvergenz; Welt